Ideologisasi Pembelajaran Aqidah di SMA Negeri 2 Kampung Rakyat Desa Perkebunan Teluk Panji Kecamatan Kampung Rakyat Kabupaten Labuhanbatu Selatan - Masaysah, Siti (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2025)
Aqidah is something that is believed by someone. The meaning of Aqidah in language will be clearer if it is associated with a terminology understanding. Through education, a person gets information and knowledge. The higher a person's education, the more information and knowledge he gets. Aqidah education is the main aspect in educating students, because with a solid Aqidah, students will know that there is a power that controls it, namely Allah SWT. Thus, the teacher's role is very decisive in conveying Aqidah education to students. The problem in the research is to look carefully at how the teacher instills aqidah in students at SMA Negeri 2 Kampung Rakyat. Aqidah is a subject that instills the basis of faith in a person. Aqidah is a person's inner state which is the source of the birth of an action. Therefore, in establishing a relationship between human beings, it must be based on Aqidah. Aqidah learning aims to foster the faith and behavior development of each student, revealing the cultivation of aqidah to describe the identity of the student's aqidah learning. This research is focused on planting Aqidah in SMAN 2 Kampung Rakyat, Teluk Panji Plantation Village, Kampung Rakyat District, Labuhan Batu Selatan Regency. which is an inhibiting and supporting factor in increasing motivation This research was carried out using a qualitative field research approach which was carried out at SMAN 2 Kampung Rakyat, Teuk Panji Plantation Village, Kampung Rakyat District, Labuhan Batu Selatan Regency. Data collection was carried out using interviews, observations and documentation. data analysis in this study by using descriptive analysis which includes: data presentation, data filtering, data classification and drawing conclusions. Testing the validity of the data obtained in this study aims to find out the description of the aqidah of students at SMA NEGERI 2 Kampung Rakyat and increase persistence or constancy of observation. The results showed that students had an understanding of aqidah learning that had been taught, because changes in student behavior or behavior were not only after learning aqidah but also caused by factors, including family, community and environmental factors where the student resided